Rhekiss - the German register for child wish and pregnancies in inflammatory rheumatic diseases - Strangfeld, Anja Maria; Meißner, Yvette; Weiß, Anja; Rudi, Tatjana; Zink, Angela; Ellmann, Tanja; Filla, Tim; Aries, Peer; Baraliakos, Xenofon; Bungartz, Christina; Glaser, Cornelia Sabine; Henes, Jörg Christoph; et al. (Pharmacoepidemiology and drug safety, 2024)
In pharmacoepidemiology, robust data are needed to judge the impact of drug treatment on pregnancy, pregnancy outcomes and breast-fed infants. As pregnant and breastfeeding women are usually excluded from randomised clinical trials, observational studies are required. One of those data sources are pregnancy registers specifically developed to focus on certain diseases or disease groups. The German Rhekiss register investigates pregnancies in women with chronic inflammatory rheumatic diseases (IRD). Rhekiss is a nationwide, multicentre, longitudinal study, in which women aged 18 years or older with an underlying IRD can be enrolled by a rheumatologist either when planning a pregnancy or in the first half of pregnancy. Data are collected prospectively at regular follow-up visits. Rheumatologists and patients provide information in a web-based system before conception (if enrolment was at the time of pregnancy planning), during and after pregnancy. A smartphone app is available for patients. Maternal and clinical information, general laboratory markers, treatment with antirheumatic and other drugs, adverse events, items related to course and outcome of pregnancy and the health of the child are uniformly assessed for all diseases. Individual information on the IRD includes classification criteria, diagnosis-specific laboratory parameters, clinical parameters and validated instruments to measure disease activity or damage. Furthermore, patient-reported outcome measures are captured. A total of 2013 individual patients have been enrolled in the register, and data on 1801 completed pregnancies are available. In summary, Rhekiss is a comprehensive and complex register that can answer various research questions about pregnancy in women with chronic IRDs.
Online veröffentlicht am 13. August 2024
Gesehen am 20.05.2025